The effects of the global surface curvature on Makyoh-topogaphy imaging - Riesz, Ferenc (Photonics Letters of Poland, 2019)
The effects of the global curvature of the reflecting surface on Makyoh (magic-mirror) topography imaging is analysed based on a geometrical optical model. It is shown that the effects can be taken into account by introducing an equivalent screen-to-sample distance which is a function of the real screen-to-sample distance and the global curvature. The special limiting cases are discussed and analysed for practical applications. Full Text: PDF References K. Kugimiya, "“Makyoh”: The 2000 year old technology still alive", J. Cryst. Growth 103, 420 (1990). CrossRef P. Blaustein, S. Hahn, "Realtime inspection of wafer surfaces", Solid State Technol. 32, 27 (1989). CrossRef Z.J. Pei, G.R. Fisher, M. Bhagavat, S. Kassir, "A grinding-based manufacturing method for silicon wafers: an experimental investigation", Int. J. Machine Tools Manufacture 45, 1140 (2005). CrossRef F. Riesz, "Makyoh topography: a simple yet powerful optical method for flatness and defect characterization of mirror-like surfaces", Proc. SPIE 5458, 86 (2004). CrossRef T. Hirogaki, E. Aoyama, R. Machinaka, H. Sueda, K. Ogawa, J. Japan Soc. Precision Eng. 73, 96 (2007). CrossRef G. Saines, M.G. Tomilin, "Magic mirrors of the Orient", J. Opt. Technol. 66, 758 (1999). CrossRef W.E. Ayrton, J. Perry, "The Magic Mirror of Japan. Part I", Proc. Roy. Soc. London 28, 127 (1878). CrossRef M.V. Berry, "Oriental magic mirrors and the Laplacian image", Eur. J. Phys. 27, 109 (2006). CrossRef F. Riesz, "Sensitivity and detectability in Makyoh imaging", Optik 122, 2115 (2011). CrossRef Z.J. Laczik, "Quantitative Makyoh topography", Opt. Eng. 39, 2562 (2000). CrossRef F. Riesz, "Geometrical optical model of the image formation in Makyoh (magic-mirror) topography", J. Phys. D: Appl. Phys. 33, 3033 (2000). CrossRef F. Riesz, "Camera length and field of view in Makyoh-topography instruments", Rev. Sci. Instr. 72, 1591 (2001). CrossRef J. Szabó, F. Riesz, B. Szentpáli, "Makyoh Topography: Curvature Measurements and Implications for the Image Formation", Japan. J. Appl. Phys. 35, L258 (1996). CrossRef F. Riesz, "Non-linearity and related features of Makyoh (magic-mirror) imaging", J. Opt. 15, 075709 (2013). CrossRef A.V. Gitin, "System approach to image formation in a magic mirror", Appl. Opt. 48, 1268 (2009). CrossRef